Comparative Epidemiological Investigation of Alzheimer’s Disease and Colorectal Cancer: The Possible Role of Gastrointestinal Conditions in the Pathogenesis of AD - Zhang, Tianlang; Han, YaRu; Wang, JianYi; Hou, Deren; Deng, Hao; Deng, Yun L.; Song, Zhi (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is a neurodegenerative disorder that affects approximately 35 million people worldwide, and diet has been reported to influence the prevalence/incidence of AD. Colorectal cancer is among the most common cancers in Western populations, and the correlation between constipation and the occurrence of colorectal cancer has been identified in a number of studies, which show that a Westernized diet is a mutual risk factor. Constipation is a growing health problem, particularly in middle-aged and older adults. As the most common gastrointestinal disorder in adults, constipation affects 2% to 20% of the world population, and it is associated with several diseases, such as diabetes, Parkinson’s disease, and others. Comparing the epidemiological data on colorectal cancer and AD, we find that colorectal cancer and AD have similar epidemiologic feature, which is both disease correlate with high prevalence of constipation. Therefore, we hypothesized that constipation may influence Alzheimer’s disease in a similar way that it contributes to colorectal cancer. This review aimed to systemically elucidate the evidence that constipation contributes toAlzheimer’s disease progression